Development and validation of small animal models for onchocerciasis and loiasis microfilaricide discovery. - Rene Bilingwe Ayiseh; Glory Enjong Mbah; Elvis Monya; Emmanuel Menang Ndi; Judy Sakanari; Sara Lustigman; Fidelis Cho-Ngwa (Public Library of Science (PLoS), 2023)
Background Onchocerciasis (river blindness) caused by the filarial worm Onchocerca volvulus is a neglected tropical disease that affects the skin and eyes of humans. Mass drug administration with ivermectin (IVM) to control the disease often suffers from severe adverse events in individuals co-injected with high loads of Loa loa microfilariae (mf). Thus loiasis animal models for counter-screening of compounds effective against onchocerciasis are needed, as are the corresponding onchocerciasis screening models. The repertoire of such models is highly limiting. Therefore, this study was aimed at developing and validating mf immunocompetent small animal models to increase tools for onchocerciasis drug discovery. Methodology/principal findings O. ochengi mf from cattle skin and L. loa mf from human blood were used to infect BALB/c mice and Mongolian gerbils, and IVM was used for model validation. O. ochengi mf were given subcutaneously to both rodents while L. loa mf were administered intravenously to mice and intraperitoneally to gerbils. IVM was given orally. In an 8-day model of O. ochengi mf in BALB/c mice, treatment with IVM depleted all mf in the mice, unlike the controls. Also, in a 2.5-day model of L. loa mf in BALB/c, IVM significantly reduced mf in treated mice compared to the untreated. Furthermore, the gerbils were very susceptible to O. ochengi mf and IVM eradicated all mf in the treated animals. In the peritoneal L. loa mf gerbil model, IVM reduced mf motility in treated animals compared to the controls. In a 30-day gerbil co-injection model, IVM treatment cleared all O. ochengi mf and reduced motility of L. loa mf. Both mf survived for up to 50 days in a gerbil co-injection model. Conclusions/significance We have developed two immunocompetent small animal models for onchocerciasis and loiasis that can be used for microfilaricide discovery and to counter-screen onchocerciasis macrofilarides.